Fortification of Traditional Medicine Manufacturers Efforts to Register Trademarks - Sulistianingsih, Dewi; Agus Sulistiyanto, Sadam (Universitas Negeri Semarang, 2024)
The brand of a product has many benefits for the progress of business, both individuals and certain legal entities, including traditional medicine manufacturers in the Nguter market, Sukoharjo Regency. However, there are many obstacles and problems that prevent manufacturers from being willing to register their traditional medicine product brands. This is certainly very unfortunate considering that traditional medicines produced by the people of Sukoharjo Regency have many benefits for consumers and have a long history. The results of the study explain that. The important function of trademark registration for traditional medicine producers in the Nguter Market area of Sukoharjo Regency is to provide certainty for brand rights owners, prevent crimes related to trademark rights, obtain exclusive rights to brands, encourage other traditional medicine producers to register their product brands. The trademark registration process for traditional medicine producers in the Nguter Market area of Sukoharjo Regency is registering yourself online or using the services of an Intellectual Property consultant or through the Regional Government of Sukoharjo Regency